Conceptions and practices of metadata quality for FRBR user tasks resources discovery in institutional repositories - Sharifah Nur Amirah binti Sarif Abdullah (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
High quality metadata represents the goodness of the records in the digital repository and make the records easily accessible to the users. Metadata quality is an important determinant to enhance the functionality of the resources in the digital repository. There is a growing awareness on the essential role of metadata quality for successful resource access and sharing across distributed digital collections. However, the proliferation of metadata records for resource discovery posed challenges for maintaining the quality of the content and growth for metadata records in the institutional repositories. Metadata quality reflects the degree to which the metadata performs the core Functional Requirements of Bibliographic Records (FRBR) user functions to find, identify, select and obtain a digital resource. The study applied a Metadata Quality Framework using three metrics, namely accuracy, consistency and completeness; and FRBR User Tasks Conceptual Model. The objectives of the study are to examine the current standard of metadata creation practices in institutional repositories, to examine metadata quality errors in institutional repositories, to investigate the perceived agreement of metadata quality and metadata quality errors among institutional repository staff, and to identify the relationship between metadata quality and FRBR user tasks. The mixed-method sequential exploratory design was used in identifying the current standard of metadata practices among local institutional repositories, determining metadata quality errors in the repositories and understanding the perceptions of institutional repository staff on the agreement of metadata quality on FRBR user tasks resource discovery. Document analysis of institutional repository websites and 378 metadata records were obtained from three selected institutional repositories in Malaysia. The questionnaire on the agreement metadata quality and metadata quality errors were gained from 50 institutional repository staff as the respondents. The findings revealed that institutional repositories in Malaysia comprehends the standard practice of metadata policy and metadata guideline. Metadata consistency was identified to have the utmost errors in the metadata records. The study also found that most of the institutional repository staff acknowledged the importance of metadata quality and metadata quality errors for resource discovery in digital repositories. The analysis indicated that metadata quality metrics of accuracy, consistency and completeness have positive effects on FRBR user tasks and should be viewed as an evolving process that necessarily relies on continuous refinement through assessment of metadata records for the future growth of institutional repositories.